The impact of postreperfusion syndrome during liver transplantation using livers with significant macrosteatosis. Issue 9 (26th March 2019) - Croome, Kristopher P.; Lee, David D.; Croome, Sarah; Chadha, Ryan; Livingston, David; Abader, Peter; Keaveny, Andrew Paul; Taner, C. Burcin
Abstract : The impact of postreperfusion syndrome (PRS) during liver transplantation (LT) using donor livers with significant macrosteatosis is largely unknown. Clinical outcomes of all patients undergoing LT with donor livers with moderate macrosteatosis (30%‐60%) (N = 96) between 2000 and 2017 were compared to propensity score matched cohorts of patients undergoing LT with donor livers with mild macrosteatosis (10%‐29%) (N = 96) and no steatosis (N = 96). Cardiac arrest at the time of reperfusion was seen in eight (8.3%) of the patients in the moderate macrosteatosis group compared to one (1.0%) of the patients in the mild macrosteatosis group ( P  = .02) and zero (0%) of the patients in the no steatosis group ( P  = .004). Patients in the moderate macrosteatosis group had a higher rate of PRS (37.5% vs 18.8%; P  = .004), early allograft dysfunction (EAD) (76.4% vs 25.8%; P  < .001), renal dysfunction requiring continuous renal replacement therapy following transplant (18.8% vs 8.3%; P  = .03) and return to the OR within 30 days (24.0% vs 7.3%; P  = .002), than the no steatosis group. Both long‐term patient ( P  = .30 and P  = .08) and graft survival ( P  = .15 and P  = .12) were not statistically when comparing the moderate macrosteatosis group to the mild macrosteatosis and no steatosis groups. Recipients of LT using livers with moderate macrosteatosis are at a significant increased risk of PRS. If patients are able to overcome the initial increased perioperative risk of using these donor livers, long‐term graft survival does not appear to be different than matched recipients receiving grafts with no steatosis. Abstract : Recipients of donor livers with moderate macrosteatosis are at a significantly increased risk of postreperfusion syndrome and cardiac arrest at the time of reperfusion.